S100A1’s single cysteine is an indispensable redox switch for the protection against diastolic calcium waves in cardiomyocytes - Seitz, Andreas; Busch, Martin; Krömer, Jasmin; Schneider, Andrea; Simon, Stephanie; Jungmann, Andreas; Katus, Hugo; Most, Patrick; Ritterhoff, Julia (American journal of physiology. Heart and circulatory physiology, 2024)
The EF-hand calcium (Ca2+) sensor protein S100A1 combines inotropic with antiarrhythmic potency in cardiomyocytes (CMs). Oxidative posttranslational modification (ox-PTM) of S100A1’s conserved, single-cysteine residue (C85) via reactive nitrogen species (i.e., S-nitrosylation or S-glutathionylation) has been proposed to modulate conformational flexibility of intrinsically disordered sequence fragments and to increase the molecule’s affinity toward Ca2+. Considering the unknown biological functional consequence, we aimed to determine the impact of the C85 moiety of S100A1 as a potential redox switch. We first uncovered that S100A1 is endogenously glutathionylated in the adult heart in vivo. To prevent glutathionylation of S100A1, we generated S100A1 variants that were unresponsive to ox-PTMs. Overexpression of wild-type (WT) and C85-deficient S100A1 protein variants in isolated CM demonstrated equal inotropic potency, as shown by equally augmented Ca2+ transient amplitudes under basal conditions and β-adrenergic receptor (βAR) stimulation. However, in contrast, ox-PTM defective S100A1 variants failed to protect against arrhythmogenic diastolic sarcoplasmic reticulum (SR) Ca2+ waves and ryanodine receptor 2 (RyR2) hypernitrosylation during βAR stimulation. Despite diastolic performance failure, C85-deficient S100A1 protein variants exerted similar Ca2+-dependent interaction with the RyR2 than WT-S100A1. Dissecting S100A1’s molecular structure-function relationship, our data indicate for the first time that the conserved C85 residue potentially acts as a redox switch that is indispensable for S100A1’s antiarrhythmic but not its inotropic potency in CMs. We, therefore, propose a model where C85’s ox-PTM determines S100A1’s ability to beneficially control diastolic but not systolic RyR2 activity. - - NEW & NOTEWORTHY S100A1 is an emerging candidate for future gene-therapy treatment of human chronic heart failure. We aimed to study the significance of the conserved single-cysteine 85 (C85) residue in cardiomyocytes. We show that S100A1 is endogenously glutathionylated in the heart and demonstrate that this is dispensable to increase systolic Ca2+ transients, but indispensable for mediating S100A1’s protection against sarcoplasmic reticulum (SR) Ca2+ waves, which was dependent on the ryanodine receptor 2 (RyR2) nitrosylation status.
Erstveröffentlichung: 31. Mai 2024
Gesehen am 28.01.2025